Cervicometría como factor predictivo de amenaza de parto pretérmino. - Cáceres Poma, Aracely Leonor (2020)
The preterm birth considered as a factor that increases the rate of perinatal morbidity and mortality, resulting in short- and long-term aftermath, which extends over the years of life, affecting childhood and adulthood, resulting in huge physical, and economic costs, which it made a major public health problem. The three main etiological causes of preterm birth threat were of idiopathic origin, by premature rupture of membranes and of iatrogenic origin. Among the most common etiological factors of idiopathic preterm birth was intraamniotic infection, deep placental defects and cervical insufficiency. The cervix is the portion of the uterus that is responsible for maintaining the pregnancy until the end, with a normal average measurement of 35 to 40 mm. The risk of preterm delivery considered to be inversely proportional to cervical length, with higher risk with a cervix less than 15mm. The measurement of cervical length in an asymptomatic woman, allows to predict an elevated risk of preterm birth, transvaginal ultrasound cervicometry being the best means for screening. Therefore, in this bibliographic review project, the importance of cervicometry as a predictive factor for preterm birth, the appropriate way to measure the cervix, at what point recommended, will be highlighted. This review will be analytical, descriptive based on the collection of 27 studies, through the analysis of these the importance of cervicometry as a predictor of preterm birth.